Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - Bi, De-Wen; Feng, Jian; Pang, Wen-Hui; Yang, Peng-Yun; Xu, Yao-Jun; Aurang Zeb, Muhammad; Wang, Meng-Ru; Zhang, Xing-Jie; Li, Xiao-Li; Zhang, Rui-Han; Wang, Wei-Guang; Xiao, Wei-Lie (Natural product research, 2024)
Three new lanostane triterpenoids (1-3) along with two new amides fatty compounds (4-5) were isolated from the ethyl acetate extract of a culture of the endophytic fungus Alternaria sp. gx-2. Their structures were identified by 1D and 2D NMR spectral data and HRESIMS. Compounds 1-12 were evaluated for their anti-inflammatory and tyrosinase inhibition activities. The isolated compounds did not show inhibitory activities at a concentration of 100 μM against tyrosinase, while under the concentration of 10 μM, the release of lactate dehydrogenase (LDH) inhibition rate of compound 1 was 54.45%, indicating that compound 1 had moderate anti-inflammatory activity on the activation of NLRP3 inflammasome.